Fluorapatite as immobilization matrix for nuclear waste. Issue 9 (3rd October 2018) - Macerata, Elena; Pizzi, Elisabetta; Ossola, Annalisa; Giola, Marco; Mariani, Mario
ABSTRACT: The safe confinement of the nuclear waste coming from fuel reprocessing operations is one of the key points in the sustainable development of the nuclear fuel cycle and, in general, of nuclear energy. Different reprocessing technologies lead to the different composition of the nuclear waste generated. Consequently, the traditional high-level waste vitrification technology is not always applicable. Therefore, alternative wasteforms were investigated. Concerning the waste generated during the pyrochemical reprocessing, several reasons made the apatites the best candidate for the immobilization of this kind of nuclear waste. This mineral is, in fact, known for its capability to accommodate in its structure a large variety of cations in different valence states. It is also characterized by good leaching and radiation resistance. In particular, interesting in environmental and materials sciences is the use of apatite to sequester radionuclides such as 90 Sr. In the present work, a new approach for the preparation of the Sr-substituted fluorapatites by solid-state reaction was investigated. The obtained apatitic phases were characterized by powder X-ray diffraction, Raman spectroscopy, Scanning Electron Microscopy and Energy Dispersive Spectroscopy. The influence of some synthesis parameters, such as the temperature, the SrF2 amount and the homogenization, was evaluated. The results suggest that the considered synthesis procedure could be reasonably applied to the confinement of Sr from different kinds of nuclear waste.